Examining the Impact of Transformational Leadership on the Strategic Decisions Effectiveness of Jordanian Microfinance Companies - Abuzaid, Ahmad Nasser; Al-Ma'aitah, Noor; Al-Haraisa, Yazan Emnawer; Al-Tarawneh, Khalaf Ibrahim (International Review of Management and Marketing, 2019)
This study aims to investigate the effect of transformational leadership on strategic decisions effectiveness. A survey method was employed for the collection of data from Microfinance companies of Jordan. The data were analyzed using Multiple Regression technique to empirically test the study hypothesis. The results demonstrate that transformational leadership positively affects strategic decisions effectiveness. Organizations should invest more to build transformational leadership capability for their managers, and provide them with adequate training programs in different aspects of transformational leadership. In addition, if these organizations are aiming to enhance strategic decisions effectiveness, they should focus on attracting and hiring managers that have a transformational leadership attributes. Moreover, they should also take into consideration the other factors like the ability to create managerial acceptance to decisions, generate new ideas, and provide innovative alternatives and choices for the enhancement of strategic decisions effectiveness. However, the current study, compared to the existing literature, contributes to the impact of transformational leadership on strategic decisions effectiveness, especially in Jordan's business settings. Keywords: Transformational Leadership; Strategic Decisions Effectiveness; Microfinance Companies. JEL Classification: M1 DOI: https://doi.org/10.32479/irmm.7562